The nucleotide in position 32 of the tRNA anticodon loop determines ability of anticodon UCC to discriminate among glycine codons. - Lustig, F (1993)
We have investigated the influence of structures in the tRNA anticodon loop and stem on the ability of the anticodon to discriminate among codons. We had previously shown that anticodon UCC, when placed in the structural context of tRNA(Gly1) from Escherichia coli, discriminated efficiently between the glycine codons, as required by the wobble rules. Thus, this anticodon read GGA and GGG but did not read GGU and GGC, whereas in mycoplasma tRNA(Gly), the same anticodon did not discriminate among the glycine codons. We have now determined the reading properties of three constructions based on tRNA(Gly1) containing the anticodon UCC in different structural contexts. In one of these constructs, tRNA(Gly1-ASL), the anticodon loop and stem are the same as in mycoplasma tRNA(Gly). The second construct, tRNA(Gly1-AS), has an anticodon stem identical with the mycoplasma tRNA(Gly), whereas in the last construct, tRNA(Gly1-C32), the only difference from tRNA(Gly1)(UCC) is that the uridine in position 32 of the anticodon loop has been replaced by cytidine. These constructs were tested for ability to read glycine codons in an in vitro protein-synthesizing system that allowed us to monitor separately the reading of each codon. We found that the anticodon UCC, when present in tRNA(Gly1-AS), discriminated among the glycine codons, whereas in the constructs tRNA(Gly1-ASL) and tRNA(Gly1-C32), the same anticodon had lost its ability to discriminate--i.e., it behaved as in mycoplasma tRNA(Gly). These results strongly suggest that nt 32 of the anticodon loop of tRNA(Gly1)(UCC) decisively influences the reading properties of the anticodon UCC.